Pengenalan Kewirausahaan di Usia Muda - Herman, Hendri; Rahmat, Muhammad (ASOSIASI IDEBAHASA KEPRI, 2024)
Entrepreneurship is one of the ways you can get a side income to improve the family's economic life. At a time when there's a lot of competition in the world of work. On the other hand, there is a labor force that has not obtained a job that corresponds to the level of education it has. There is also a labour force that does not get a job because it does not have an education. Therefore, in addition to obtaining side income, entrepreneurship is one of the ways that can be done to make a living, because it is the only source of income. The first step that can be taken to foster entrepreneurial interest is the construction of entrepreneurship where the source is the source that really struggles in the business world so that it can motivate the participants. This dedication will be held in the Pondok Pesantren Ruhul Qur'an that lies in the Mediterranean extension Blk HH 3 A no. 18-23. This dedication is a young age, so it is worthy to be given an understanding and insight into entrepreneurship so that it can be one of the sources of economic income in the future. This dedication is expected to make a positive contribution to the participants